STUDI KELAYAKAN PEMBUKAAN CABANG BARU BARBERSHOP TEXAS DI KOTA BATAM - Gulo, Darianus; Sirait, Ganda (LPPM Universitas Putera Batam, 2021)
The purpose of this study is to assess the feasibility of establishing a branch of the Texas Barbershop in Batam city. To find out the feasibility of the Texas Barbershop business in terms of several aspects, namely market aspects, technical aspects, management aspects and financial aspects. Based on an assessment of market aspects, the opening of a Texas Barbershop branch is deemed worthy of being seen from the increase in the number of people who become its market share each year. Analysis of the technical aspects shows that the location and layout of the business premises can save additional costs. So, this business assessment in terms of technical aspects is declared feasible to run. Analysis of the management aspect shows that the owner of the Texas barbershop is willing to meet the criteria needed in the organization, both in recruiting employees, retaining employees and paying employee wage obligations according to their position and level in the process of running a business. From a financial perspective, the difference between income and expenditure results in a positive net cash calculation. In financial calculations, the results obtained Net present value (NPV) of IDR 24,791,334.9 Rupiah, payback period (PP) for 1.39 years, profitability index (PI) of 2.42 times and average rate of return (ARR) by 80.4%.